Streamflow Simulation for Nam Xong River Basin in Vang Vieng District, Vientiane Province: https://doi.org/10.69692/SUJMRD1001202-213 - SISOUPHANTHAVONG , Bounteum; Sivanpheng, Ounla; Kimmany, Bounhome (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
Nam Xong River is one of the tributaries of Nam Lik River, which is considered an important river that creates natural tourism value for the people in Vang Vieng District. Nam Xong Dam was another dam built to generate electricity and divert water to Nam Ngum 1 reservoir to increase hydropower generation capacity. Recently, Nam Xong River Basin (NXRB) has been affected by flooding almost every year due to changes in the amount and pattern of rainfall which is highly variable. Another issue is aggravated by the problem of ungauged basins where the number of hydrological and meteorological stations are limited and unequally distributed over the basins. This obstructs the reliability of streamflow prediction and water resources management. This study therefore aims to address the problems of ungauged basins by performing tasks that serve a main objective: application of HEC-HMS for simulating the streamflow for NXRB. The hydrological and meteorological data used in this study are daily streamflow 2 stations and rainfall 4 stations located in and around the basin. The simulation period is considered based on random flood events from 2005 to 2021. Out of these, 5 events (2005-2015) are selected for model calibration and another event of 2021 are considered for model validation. The results found that the HEC-HMS model can estimate the flow rate in accordance with the observed data, especially during the low flow period. Throughout the considered period, the average flow and total flow volume showed a downward trend. For the result of estimating the maximum flow from the model, the streamflow is lower than the observed data, and the time to peak from the model comes about 1 day later than the observed one in 2014, probably due to the distribution of rainfall in the study area with high variability. Therefore, the HEC-HMS model could be used to simulate daily streamflow in limited data areas. This study could provide recommendations for hydrological modeling for other basins that have similar characteristics to the NXRB.